A Review on Bond and Anchorage of Confined High-strength Concrete. (August 2017) - Sulaiman, Muhd Fauzy; Ma, Chau-Khun; Apandi, Nazirah Mohd; Chin, Sofrie; Awang, Abdullah Zawawi; Mansur, Shaiful Amri; Omar, Wahid
Abstract: The interaction between reinforcement bars and concrete is particularly essential in predicting the ultimate failure of reinforced concrete (RC) elements. It is particularly important to understand the bond and anchorage behaviour of reinforcement bars with the surrounding concrete. The current codes of practice in designing anchorage length in high-strength concrete (HSC) were scarce and were extrapolated from the experimental results of normal strength concrete (NSC). It has been consistently being reported that the bond and anchorage of bars in HSC are relatively weaker compared to in NSC. Even various studies had been conducted in studying the bond and anchorage in conventional RC but the applications of these codes of practice are unsuitable for HSC. This problem makes a barrier for a widespread utilization of HSC in the construction industries. In view of this, this study reviewed previous studies of bond and anchorage behaviour of reinforced NSC and HSC, their mechanisms and applicability of using confining pressure in developing bond and anchorage in facilitating the research development in bond and anchorage behaviour of RC structures. The findings showed that the confinement is effective in enhancing bond and anchorage between reinforcement bars and concrete but further research is still needed to develop adequate guidelines over a service of long term for RC with lateral or transverse confinement Highlights: With the increase of concrete compressive strength, the bond and anchorage of reinforced concrete become higher. The design of bond and anchorage for high-strength concrete is largely based on the experimental results of normal strength concrete. Pull-out test is commonly used to determine bond strength of embedded reinforcement, while simply supported beam is the test used to evaluate lap splice and end anchorage behaviour. Confinement has been reported to have increase the bond and anchorage of high-strength concrete.